2006
DOI: 10.1158/0008-5472.can-05-1667
|View full text |Cite
|
Sign up to set email alerts
|

3p21.3 Tumor Suppressor Gene H37/Luca15/RBM5 Inhibits Growth of Human Lung Cancer Cells through Cell Cycle Arrest and Apoptosis

Abstract: Deletion at chromosome 3p21.3 is the earliest and the most frequently observed genetic alteration in lung cancer, suggesting that the region contains tumor suppressor gene(s) (TSG). Identification of those genes may lead to the development both of biomarkers to identify high-risk individuals and novel therapeutics. Previously, we cloned the H37/Luca15/RBM5 gene from 3p21.3 and showed its TSG characteristics. To investigate the physiologic function of H37 in the lung and its mechanism of tumor suppression, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 28 publications
8
96
0
Order By: Relevance
“…RBM5 expression is repressed in 70-80% of lung cancers (25). RBM5 overexpression causes cell cycle arrest, apoptosis, and inhibition of tumor growth (25)(26)(27)29), sensitizing cells to apoptosis induced by death receptor ligands, FAS, TNF-␣, and TRAIL (31,32). However, the mechanism for this sensitization was not known.…”
Section: Discussionmentioning
confidence: 99%
“…RBM5 expression is repressed in 70-80% of lung cancers (25). RBM5 overexpression causes cell cycle arrest, apoptosis, and inhibition of tumor growth (25)(26)(27)29), sensitizing cells to apoptosis induced by death receptor ligands, FAS, TNF-␣, and TRAIL (31,32). However, the mechanism for this sensitization was not known.…”
Section: Discussionmentioning
confidence: 99%
“…It was soon realized that this encoded an inhibitory RNA complementary to the 39 untranslated region (UTR) of the RBM5 mRNA, and that full-length, sense-oriented RBM5 actually potentiates apoptosis initiated by Fas (Rintala-Maki and Sutherland 2004). In addition to its role in apoptosis, expression of RBM5 has been found to inhibit proliferation when transfected into several different cell lines (Edamatsu et al 2000;Oh et al 2006). RBM5 also appears to stimulate p53 transcription and promote higher levels of p53 transcripts through an unknown mechanism (Kobayashi et al 2010).…”
Section: Rna-binding Motif 5 (Rbm5)mentioning
confidence: 99%
“…The growing literatures on H37 strongly suggest its involvement in apoptosis and cell cycle regulation, with all results converging on a role for H37 as a TSG. Using the lung cancer cell model, we showed that H37 clearly inhibits tumour growth both in vitro and in vivo with antitumour mechanisms involving cell cycle (G1) arrest and apoptosis [11]. H37 also mediates growth inhibition by eliciting reduced expression of cyclin A and pRB as well as by increased expression of pro-apoptotic protein Bax [11].…”
Section: Introductionmentioning
confidence: 95%
“…Using the lung cancer cell model, we showed that H37 clearly inhibits tumour growth both in vitro and in vivo with antitumour mechanisms involving cell cycle (G1) arrest and apoptosis [11]. H37 also mediates growth inhibition by eliciting reduced expression of cyclin A and pRB as well as by increased expression of pro-apoptotic protein Bax [11]. Consistently, H37 triggers mitochondrial apoptotic pathways downstream of Bax, in a p53-independent manner, which include breakdown in the mitochondrial membrane potential, cytochrome c release into cytosol, and enhanced caspase-9 and caspase-3 activities [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation